2014
DOI: 10.3390/ma7075169
|View full text |Cite
|
Sign up to set email alerts
|

New Gold Nanostructures for Sensor Applications: A Review

Abstract: Gold based structures such as nanoparticles (NPs) and nanowires (NWs) have widely been used as building blocks for sensing devices in chemistry and biochemistry fields because of their unusual optical, electrical and mechanical properties. This article gives a detailed review of the new properties and fabrication methods for gold nanostructures, especially gold nanowires (GNWs), and recent developments for their use in optical and electrochemical sensing tools, such as surface enhanced Raman spectroscopy (SERS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 122 publications
0
95
0
4
Order By: Relevance
“…Moreover, CNFs prevent self-aggregation of GNPs, which determine an enhancement in accessible sites of nanocomposite. 43,44 Therefore, it can be concluded that CNFs and GNPs have synergistic effects.…”
Section: Results and Discussion Electrochemical Properties Of Cnf-gnpmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CNFs prevent self-aggregation of GNPs, which determine an enhancement in accessible sites of nanocomposite. 43,44 Therefore, it can be concluded that CNFs and GNPs have synergistic effects.…”
Section: Results and Discussion Electrochemical Properties Of Cnf-gnpmentioning
confidence: 99%
“…43 At the same time, gold nanoparticles (GNPs) have also been shown to display great conductivity, enhanced electrocatalytic activity and biocompatibility. 44 Therefore, it can be expected that a synergistic effect of both CNFs and GNPs (CNF-GNP) together can lead to a highly sensitive voltamperometric sensor for the determination of pyritinol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the AuNPs deposited on the walls of the silicon in the porous matrix act as an additional source to improve the surface area and hence enhance the gas adsorption rate (Zhang and Chu 2014), while the embedded gold nanoparticle inside the pores itself will damp the activity of the pores, so the current will decrease. The relative response of the current of the (S) was calculated using the following relation:…”
Section: Electrical Characterizationmentioning
confidence: 99%
“…Careful selection and design of ligands strongly influence the sensitivity and selectivity of a sensor. 5,11 Gold nanoparticles can be synthesized by a citrate reduction method pioneered by Turkevich 12 and later advanced by Frens, 13 with a variety of modification's methods. 6,[14][15][16][17][18] The nanoparticle morphology is dependent upon chemical nanoparticle synthesis methods.…”
Section: -8mentioning
confidence: 99%